Neurodegenerative and Neurobehavioral Symptoms in Jember Agricultural Workers Caused by Oxidative Stress and Neurotransmitter Disturbance - Narwanto, Muhammad Ihwan; Purwandhono, Azham; Sofiana, Kristianningrum Dian; Febianti, Zahrah; Jauhani, Muhammad Afiful; Kusumastuti, Inke; Putri, Elvia Rahmi Marga (Majalah Kedokteran Bandung, 2024)
Increased use of pesticides can have detrimental health consequences, one of which is chronic neurotoxicity. The symptoms include degenerative and neurobehavioral issues. Chronic neurotoxicity occurs through oxidative stress, inflammation, and neurotransmitter disturbances. This study aimed to determine chronic neurotoxicity and test malondialdehyde and cholinesterase levels as neurotoxicity biomarkers among agricultural workers in Wuluhan, Jember, Indonesia. The 60-person research sample was divided into two groups: agricultural and non-agricultural workers. The interview utilized a mini-mental score examination, Chan's questionnaire, and the Patient Health Questionnaire to analyze the cognitive impairment, Parkinsonism, and depressive symptoms. The examination of serum malondialdehyde levels was performed using the TBARS method and cholinesterase levels by photometric kinetic method at a biochemistry laboratory from October to November 2022. Results showed cognitive impairment and depressive symptoms in agricultural workers, as well as high levels of malondialdehyde and low cholinesterase levels. This study concludes the presence of chronic pesticide neurotoxicity among agricultural workers in Jember, Indonesia, and that malondialdehyde and cholinesterase levels might serve as biomarkers of pesticide-induced neurotoxicity.